Altruistic Punishment and Impulsivity in Parkinson’s Disease: A Social Neuroscience Perspective - Morese, Rosalba; Palermo, Sara (Frontiers in Behavioral Neuroscience, 2020)
Non-motor symptoms of Parkinson's disease are of increasing interest in clinical and psychological research. Disinhibition - the inability to inhibit inappropriate behaviour – leads to social and emotional impairments, including impulsive behaviour and disregard for social conventions and decision-making behavior. In recent years, the latter has been investigated using economic exchanges during social interactions. Altruistic punishment – to punish someone who violates group norms even if it foresees a personal cost - is one of the most useful and fruitful paradigms, it allows to maintain a cooperation system within social groups. Alterations of this cognitive ability negatively impact the quality of life of the individual and social stability. Social neuroscience has suggested association between impulsive behaviours and altruistic punishment. Neuroimaging research aimed at exploring functional networks and intrinsic functional connectivity went in this direction. To date, little is known about these issues in neurodegenerative diseases such as Parkinson's disease (PD). Dopamine replacement treatment and dopamine-agonists have been associated with impulse-control disorder and impulsive-compulsive behaviour able to affect social decision-making. Frontal-executive dysfunction determines an alteration of social functioning through a mechanism of subversion of online action-monitoring, which associates disinhibition with volition. Genetic polymorphisms, alterations of the nigro-striatal substance, impairment in the medial prefrontal cortex and in the Default Mode Network seem to be able to explain these mechanisms. This theoretical perspective article aims to present these topics in order to encourage an interdisciplinary discussion capable of generating new research and developing rehabilitative intervention to improve social decision-making in PD patients.